NEW RECORD OF SPECIES URENTIUS EUONYMUS 1909 (HEMIPTERA: HETEROPTERA: TINGIDAE) IN BAGHDAD - & Hamodi, Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A new record of lace bug species Urentius euonymus (family :Tingidae) belongs to (order: Hemiptera and sub order Heteroptera) at first time in Iraq which is collected three hundred five (350) insects (males and females) from leaves of weed Chrozophora tinctoria (family: Euphorbiaceae) from college of Agriculture Abu- Gharib at 20 / 7 /2017 ,and Al- jaderia at 11/9/2017, insects Indented by used a taxonomic keys, morphological characters was described. Used camera Lucida to draw bodies’ part and picture by digital camera.